Salivary Free Testosterone and Gingival Health Condition among a Group of Women with Polycystic Ovary Syndrome - Andalus Abid Hassan Tahir; Baydaa Hussien (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting women in their reproductive age.It is characterized by anovulation or oligo-ovulation and hyperandrogensim.Androgen excess is the central defect in polycystic ovary syndrome. It is a complex disorder affects general health in addition to oral health.This study aimed to assess the gingival health status among a group of women with polycystic ovary syndrome as well as to estimate the levels of salivaryfree testosterone in unstimulated saliva in relation to gingival health condition. Materials and methods: Sixty two women with an age range 20-25 years old and with a body mass index range18.5-24.9 (normal weight) were included in this study. They were divided into two groups; the study group which included thirty one women with polycystic ovary syndrome, those women. nattended Babylon Teaching Hospital/ Infertility Center and the control group which included thirty one women with regular menstrual cycles,without clinical or biochemical features of hyperandrogenism and ultrasound exclusion of polycystic ovary (without polycystic ovary syndrome). Collection of unstimulated salivary samples was carried out under standardrizedconditions, salivary free testosterone levels were estimated. Plaque index of Silness and Lӧe (1964) was used to assess dental plaque. While gingival index of Lӧe and Silness (1963) was used to assess gingival inflammation. Data analysis was conducted through the application of the (SPSS version 18). The analysis of data included: Mean, Standard deviation, t-test, Pearson Correlation (r), Receiver Operative Characteristics Curve (ROC curve). Results:Results showed that the mean value of plaque index was found to be higher in the control group (1.18±0.03) than that in the study group (1.00±0.08) with statistically highly significant difference (p